2002
DOI: 10.1038/nature01051
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying nitrogen-fixation in feather moss carpets of boreal forests

Abstract: Biological nitrogen (N) fixation is the primary source of N within natural ecosystems, yet the origin of boreal forest N has remained elusive. The boreal forests of Eurasia and North America lack any significant, widespread symbiotic N-fixing plants. With the exception of scattered stands of alder in early primary successional forests, N-fixation in boreal forests is considered to be extremely limited. Nitrogen-fixation in northern European boreal forests has been estimated at only 0.5 kg N ha(-1) yr(-1); howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
435
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(463 citation statements)
references
References 24 publications
21
435
2
5
Order By: Relevance
“…This is on the same order of magnitude as the range of 12-25 kg ha −1 y −1 reported for pristine boreal bogs, although their growing season only lasts 140 days per year (Vile et al, 2014). Furthermore, similar to Markham (2009), we found Sphagnum-associated N 2 fixation rates to be at least 5 times higher than those found in feather mosses, which are around 1.5-3 kg ha −1 yr −1 (Rousk et al, 2014;DeLuca et al, 2002;Zackrisson et al, 2009;Leppänen et al, 2013). This could be due to morphological differences between the moss species (including hyaline cells of Sphagnum providing additional space and protection to microorganisms) and differences in microbial communities resulting from differences in habitat conditions and resources, i.e., availability of inorganic and organic nitrogen and carbon compounds, moisture content and presence of oxygen.…”
Section: Diazotrophic Activity Under High N Conditionssupporting
confidence: 70%
“…This is on the same order of magnitude as the range of 12-25 kg ha −1 y −1 reported for pristine boreal bogs, although their growing season only lasts 140 days per year (Vile et al, 2014). Furthermore, similar to Markham (2009), we found Sphagnum-associated N 2 fixation rates to be at least 5 times higher than those found in feather mosses, which are around 1.5-3 kg ha −1 yr −1 (Rousk et al, 2014;DeLuca et al, 2002;Zackrisson et al, 2009;Leppänen et al, 2013). This could be due to morphological differences between the moss species (including hyaline cells of Sphagnum providing additional space and protection to microorganisms) and differences in microbial communities resulting from differences in habitat conditions and resources, i.e., availability of inorganic and organic nitrogen and carbon compounds, moisture content and presence of oxygen.…”
Section: Diazotrophic Activity Under High N Conditionssupporting
confidence: 70%
“…However, a wide span of values ranging between 0.56 and 22 has been reported in studies from terrestrial ecosystems (summarized in Liengen, 1999a). Studies on N 2 fixation in northern ecosystems reported ratios 0.022-4.9 (Liengen, 1999a;DeLuca et al, 2002;Sorensen et al, 2006). The reason for the relatively high conversion factor in our soils can be explained by low nitrogenase activity, but remains inconclusive.…”
Section: Data Analysesmentioning
confidence: 58%
“…Many studies also documented an association of Nostoc sp. with Pleurozium schreberi (DeLuca et al, 2002;Houle et al, 2006;Gundale et al, 2012). However, soil cores covered with this moss species were the only ones from vegetated PP that did not exhibit any nitrogenase activity in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, bryophytes are very efficient in assimilating N, which are competitive scavengers of N and can reduce N availability of vascular plants, because bryophytes can not only absorb N from soil directly but can also fix atmospheric N 2 by forming facultative symbioses with cyanobionts (DeLuca et al 2002;Turetsky 2003;Ayres et al 2006). In addition, bryophytes absorb more ammonium-N than nitrate-N and glycine-N.…”
Section: Discussionmentioning
confidence: 99%